Clarendon and the Rhetoric of Historical Form - Brownley, Martine Watson (The Middle Ages Series, 2016)
Clarendon and the Rhetoric of Historical Form is the first major evaluation from a literary point of view of the writings of Edward Hyde, the first Earl of Clarendon and the most important English historiographer of the seventeenth century.